ANALISIS PENERAPAN MANAJEMEN KARIR PEGAWAI PADA KANTOR KECAMATAN TUHEMBERUA KABUPATEN NIAS UTARA - MEIMAN JAYA GEA; CARDINAL MENDROFA; EDUAR BAENE (JURNAL ILMIAH SIMANTEK, 2022)
This research is the application of employee career management at the Tuhemberua District Office, North Nias Regency. Data collection techniques using the method of documentation and interviews. The purpose of this study was to determine the application of career management at the Tuhemberua District Office, North Nias Regency. All positions at the Tuhemberua District Office have been filled by civil servants who have been assigned to the Tuhemberua District Office. In the informant's statement it is known that the employee's career development process has not developed properly due to several factors such as education, age and years of service of the employee.